1994
DOI: 10.4049/jimmunol.152.2.496
|View full text |Cite
|
Sign up to set email alerts
|

Environmental signals influencing expression of the IFN-gamma receptor on human T cells control whether IFN-gamma promotes proliferation or apoptosis.

Abstract: IFN-gamma R expression is subject to contrasting modulation on human T cells. IFN-gamma R constitutive expression is low on three human malignant T cells (ST4, PF382, and Jurkat) growing in medium supplemented with serum. The addition of IFN-gamma down-modulates IFN-gamma R expression and increases both proliferation and MHC class I Ag expression. By contrast, when malignant T cells are cultured in medium without serum, IFN-gamma R expression dramatically increases and the cells undergo a slow apoptotic death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Programmed cell death (PCD) can be triggered externally through the activation of various cell surface receptors. Among the physiological triggers of PCD, a group of cytokines plays a crucial role, including both diffusible cytokines such as TNF‐α, interferon‐γ (IFN‐γ) and TGF‐β, and membrane‐bound proteins such as the ligand to Fas/APO‐1 receptor (Laster et al ., 1988; Trauth et al ., 1989; Itoh et al ., 1991; Lin and Chou, 1992; Novelli et al ., 1994). These findings led to the concept that exposure of cell cultures to a specific cytokine may provide a well‐controlled in vitro system for the isolation of genes that mediate PCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed cell death (PCD) can be triggered externally through the activation of various cell surface receptors. Among the physiological triggers of PCD, a group of cytokines plays a crucial role, including both diffusible cytokines such as TNF‐α, interferon‐γ (IFN‐γ) and TGF‐β, and membrane‐bound proteins such as the ligand to Fas/APO‐1 receptor (Laster et al ., 1988; Trauth et al ., 1989; Itoh et al ., 1991; Lin and Chou, 1992; Novelli et al ., 1994). These findings led to the concept that exposure of cell cultures to a specific cytokine may provide a well‐controlled in vitro system for the isolation of genes that mediate PCD.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies were raised and the and membrane-bound proteins such as the ligand to Fas/ expression of the proteins was studied. It was found that APO-1 receptor (Laster et al, 1988;Trauth et al, 1989;Itoh et al, 1991;Lin and Chou, 1992;Novelli et al, DAP-1 codes for a 15 kDa proline-rich basic protein, that DAP-2 is a structurally unique 160 kDa serine/threonine Immunostaining and biochemical fractionations revealed that the kinase is localized to the cytoskeleton in associ-protein kinase (therefore named DAP-kinase), and that DAP-3 codes for a 46 kDa protein that carries a potential ation with the microfilament system and defined a region downstream of the first P-loop motif which contributes to ATP/GTP binding motif Kissil et al, 1995).…”
mentioning
confidence: 99%